Dementia as Risk Factor for Severe Coronavirus Disease 2019: A Case-Control Study - Pisaturo, Mariantonietta; Calò, Federica; Russo, Antonio; Camaioni, Clarissa; Giaccone, Agnese; Pinchera, Biagio; Gentile, Ivan; Simeone, Filomena; Iodice, Angelo; Maggi, Paolo; Coppola, Nicola (Frontiers in Aging Neuroscience, 2021)
Background: The aim of the present study was to investigate the outcome of patients with SARS-CoV-2 infection and dementia. Patients and methods: In a multicenter, observational, 1:2 matched case-control study all 23 patients with a history of dementia, hospitalized with a diagnosis of SARS-CoV-2 infection from February 28th 2020 to January 31st 2021 were enrolled. For each Case, 2 patients without dementia observed in the same period study, pair matched for gender, age (+5 years), PaO2 / FiO2 (P/F) ratio at admission (<200, or >200), number of comorbidities (+1; excluding dementia) were chosen (Control group). Results: The majority of patients were males (60.9% of Cases and Controls) and very elderly [median age 82 years (IQR: 75.5-85) in the Cases and 80 (IQR: 75.5-83.75) in the Controls]. The prevalence of co-pathologies was very high: all the Cases and 43 (93.5%) Controls showed a Charlson comorbidity index of at least 2. During hospitalization the patients in the Case group less frequently had a moderate disease of COVID-19 (35% vs. 67.4%, p=0.02), more frequently a severe disease (48% vs. 22%, p=0.03) and more frequently died (48% vs. 22%, p=0.03). Moreover, during COVID-19, 14 (60.8%) patients in the Case group and 1 (2.1%; p<0.000) in the Control group showed signs and symptoms of delirium. Conclusion: Patients with dementia are vulnerable and have an increased risk of a severe disease and death when infected with COVID-19.